Green Packaging as a Branding Strategy: How Eco-Friendly Materials Influence Brand Image and Customer Loyalty - Dwi Nita Aryani; Ng Wei Chen; Gan Kia Hui; Koh Teng Wei; Khor Ming Hooi; Lee Yi Ching; Kashwini A/P Kesavan; Afizah Sabrina Ainurohmah; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Plastic pollution and rising sustainability awareness have shifted consumer expectations toward environmentally responsible packaging. This study examines how green packaging influences brand equity and customer loyalty, focusing on Quaker Oats Malaysia. It specifically investigates the roles of environmental awareness, customer perception, willingness to pay, and brand image, with brand equity serving as a mediating variable. A quantitative survey of 150 Malaysian consumers aged 18–44 was conducted and analyzed using multiple regression in SPSS. The results indicate that willingness to pay (? = 0.323, p 0.01), brand image (? = 0.745, p 0.001), and brand equity (? = 0.367, p 0.01) significantly affect customer loyalty and brand strength. Environmental awareness also positively affects brand equity (? = 0.161, p 0.05) but has no direct effect on loyalty. Mediation analysis confirms that brand equity fully mediates the effects of environmental awareness and brand image on loyalty, explaining 64.6% of the variance in loyalty and 73.4% in equity. These findings emphasize that sustainability-driven brand equity transforms ethical initiatives into customer trust and long-term loyalty, making green packaging both an environmental and strategic advantage for consumer brands.